Skinput: Appropriating the Skin as an Interactive Canvas. (Communications of the ACM, 2011)
The article examines Skinput, a technology in which skin on the human body can be employed as computer input-output equipment by the analysis of mechanical vibrations throughout the body. The technology's use of a sensor array worn as an armband is considered, particularly its employment as an on-body finger input system that is both portable and minimally invasive. The coupling of Skinput with a pico-projector to create an interactive graphical interface directly on the human body is discussed.